(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: The purpose of this study is to evaluate the efficacy of hybrid-ceramic endocrown design on premolars in terms of retention Keywords: endocrown, conservatism, ceramics, hybrid-ceramics, retention, endocrown-design, endodontically treated premolars Methodology: Twenty-four sound maxillary premolars were endodontically treated. Group (B) received endocrown, with butt joint finish line fabricated from (CERASMART, GC Dental, USA). Group (F) received endocrown, with ferrule finish line fabricated from (CERASMART, GC Dental, USA). All restorations were fabricated using (CEREC MC XL SW 5.0) and cemented using self-adhesive dual cure resin cement (DUO-LINK UNIVERSAL, Bisco Inc, Schaumburg, IL, USA). All samples were subjected to thermocycling. To test the retention, a universal testing machine was used, the endocrowns were pulled out along the path of insertion by double orthodontic wire loops through lateral projections made during designing and production of the restorations. The forces required for dislodgment of the crowns were recorded in Newtons. Results: Retention test showed that endocrown with ferrule design have statistically significant higher values of retention than endocrown with butt-joint design Conclusion: All obtained retention values lie within the clinically accepted ranges. Endocrown with 2 mm ferrule has superior retention than those without ferrule (butt joint) on premolars.